Materiality of visuality. About relationships and transformations of visuality and politics - Lompe, Maria; Wicher, Cezary (Humaniora. Czasopismo Internetowe, 2020)
In the hazy anthropocene era, which M. Chaberski (2019) understood as a serious epistemological crisis, even wider than the climate crisis, visuality plays a very important role -it becomes a vector for visibility and invisibility of discursive and non-discursive practices. The spirit of new materialism has developed a number of concepts, which emphasized non-linguistic ways of shaping meanings and interpretations of reality, and at the same time appreciated non-humans agencies. The article is constructed around the thesis “visual is material,” because in the end every representation refers to the materials, on which our world is build. We can treat this thesis as a political statement, following J. Ranciere observations, that the thought is material (2007). We would like to analyze the significance of materiality by taking a look at media art practices. We can sink into the thicket of connections between materials and track the journey of things, not focusing on the final effect (manufactured item), but rather on manufacturing process (Ingold 2019; Deleuze, Guattari 2015).